Enhancing the Lifting Capacity of Drilling Fluids in Vertical Oil Wells - Assi, Amel habeeb (Iraqi Journal of Chemical and Petroleum Engineering, 2017)
Of the many functions that are performed by the drilling fluid, the most important is to transport cuttings from the bit up the annulus to the surface. Various drilling fluid have been widely used in the oil industry to improve lifting capacity. In this study, three mud type have been used which they are, oil base mud, X-anthan polymer and a mixture of CMC and bentonite ,by using Carrying Capacity Index calculation (CCI) , the Xanthan gave good values of CCI than other studied drilling fluid. By using Sifferman chart and field data from well in south of Iraq and API equation to find cutting concentration in the annulus, The results showed that the used of thick mud increase the lifting capacity and decrease volumetric drill cuttings in the annulus but the using thin mud lead to decrease lifting capacity and increase volumetric drill cuttings in the annulus .The results show that the mud viscosity and flow rate have important role in hole cleaning. Also, the effect of annulus velocity and flow pattern on cutting transport ratio is studied by using field data. The effect of cutting size and OD of drill pipe is also studied. Cutting size is one of the parameters that influence the hole cleaning; large size cutting makes the hole cleaning more difficult. The reducing of annular size of hole by increasing the OD of drill pipe lead to increasing the annular velocity.